Seasonal variation of auxin in stem cambial region of Pinus sihestris L. - Tomasz J. Wodzicki (Acta Societatis Botanicorum Poloniae, 2015)
Investigation of auxin from the stem cambial region of adult Pinus silvestris trees by diffusion to agar, and by extraction revealed both seasonal variation and gradients along the stem. Variation in dynamics of auxin efflux and the effect of the size of tissue blocks are used as arguments in the critical discussion of the concept of auxin regulation of cambial activity by way of simple seasonal concentration changes.